Studia Doctoralia 2019
DOI: 10.47040/sd/sdpsych.v10i1.88
|View full text |Cite
|
Sign up to set email alerts
|

The role of locus of control and self-perception in the relationship between cyberbullying and depression, anxiety and stress in emerging adults

Abstract: The present study aims at identifying the mediator role of the self-perception and the moderator role of locus of control in the relationship between cyberbullying and depression, anxiety, and stress symptoms. Seventy-two emerging adults between 20 to 25 years old were included in the study, filling in a series of measuring instruments for cyberbullying, self-perception, locus of control and depression, anxiety, and stress symptoms. The results were statistically significant in terms of the role of self-percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 66 publications
0
3
1
Order By: Relevance
“…Therefore, Hypothesis 3, regarding this mediating role, was not supported. This finding is not in line with previous studies, which have found that students’ external or internal locus of control could make them more or less vulnerable, respectively, to cyberbullying engagement as bullies/victims (Özdemir & Bektaş, 2021; Popoviciu, 2019). This feeling of control likely has the potential to interact with individuals’ behaviors (as victims/bullies), especially in the cases where something happens to themselves (being victimized/victimize others), compared to the cases where a negative incident (cyberbullying) happens to others and a bystander has to decide over controlling the situation.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Therefore, Hypothesis 3, regarding this mediating role, was not supported. This finding is not in line with previous studies, which have found that students’ external or internal locus of control could make them more or less vulnerable, respectively, to cyberbullying engagement as bullies/victims (Özdemir & Bektaş, 2021; Popoviciu, 2019). This feeling of control likely has the potential to interact with individuals’ behaviors (as victims/bullies), especially in the cases where something happens to themselves (being victimized/victimize others), compared to the cases where a negative incident (cyberbullying) happens to others and a bystander has to decide over controlling the situation.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, individuals' low empathic skills could make them ineffectively decode and feel others' emotions and meanings during online chatting and therefore easily become the target of online victimization (Brewer & Kerslake, 2015;Horzum et al, 2021). Accordingly, the locus of control, namely, the way individuals perceive that a situation is under their control (internal locus of control) or not (external locus of control), could predispose them more or less positively, respectively, to appropriately manage an online conversation and avoid getting involved in an unpleasant experience as a bully or victim (e.g., Özdemir & Bektaş, 2021;Popoviciu, 2019). However, despite the intense research interest in the predictive role of empathy and locus of control in cyberbullies and cybervictims, the investigation of the predictive value of the above individual factors in case of bystanders' intended reaction to cyberbullying is scarce, inconclusive, and concerns almost exclusively adolescents and not young adults as mentioned previously.…”
Section: The Role Of Context-related and Individual Contributorsmentioning
confidence: 99%
See 2 more Smart Citations